Effects of mindfulness practice on performance-relevant parameters and performance outcomes in sports: A meta-analytical review - Bühlmayer, L.; Birrer, D.; Röthlin, P.; Faude, O.; Donath, L. (Sports Medicine, 2017)
Background: Mindfulness as a present-oriented form of mental training affects cognitive processes and is increasingly considered meaningful for sport psychological training approaches. However, few intervention studies have examined the effects of mindfulness practice on physiological and psychological performance surrogates or on performance outcomes in sports. Objective: The aim of the present meta-analytical review was to examine the effects of mindfulness practice or mindfulness-based interventions on physiological and psychological performance surrogates and on performance outcomes in sports in athletes over 15 years of age. Data Sources: A structured literature search was conducted in six electronic databases (CINAHL, EMBASE, ISI Web of Knowledge, PsycINFO, MEDLINE and SPORTDiscus). The following search terms were used with Boolean conjunction: (mindful* OR meditat* OR yoga) AND (sport* OR train* OR exercis* OR intervent* OR perform* OR capacity OR skill*) AND (health* OR adult* OR athlete*). Study Selection: Randomized and non-randomized controlled studies that compared mindfulness practice techniques as an intervention with an inactive control or a control that followed another psychological training program in healthy sportive participants were screened for eligibility. Data Extraction: Eligibility and study quality [Physiotherapy Evidence Database (PEDro)] scales were independently assessed by two researchers. A third independent researcher was consulted to achieve final consensus in case of disagreement between both researchers. Standardized mean differences (SMDs) were calculated as weighted Hedges` g and served as the main outcomes in comparing mindfulness practice versus control. Statistical analyses were conducted using a random-effects inverse-variance model. Results: Nine trials of fair study quality (mean PEDro score 5.4, standard deviation 1.1) with 290 healthy sportive participants (athletics, cyclists, dart throwers, hammer throwers, hockey players, hurdlers, judo fighters, rugby players, middle-distance runners, long-distance runners, shooters, sprinters, volleyball players) were included. Intervention time varied from 4 weeks to over 2 years. The practice frequency lasted from twice daily to just once a week, and the mean session time covered 50-60 min. In favor of mindfulness practice compared with the control condition, large effects with narrow confidence limits and low heterogeneity were found for mindfulness scores [SMD 1.03, 90% confidence interval (CI) 0.67-1.40, p < 0.001, I2 = 17%]. Physiological performance indices depicted wide confidence limits accompanied with very large heterogeneity. However, the effect sizes remained very large, with confidence limits that did not overlap zero (SMD 3.62, 90% CI 0.03-7.21, p = 0.10, I2 = 98%). Moderate to large effects were observed for both psychological performance surrogates (SMD 0.72, 90% CI 0.46-0.98, p < 0.001, I2 = 14%) and performance outcomes in shooting and dart throwing (SMD 1.35, 90% CI 0.61-2.09, p = 0.003, I2 = 82%). Conclusions: Mindfulness practice consistently and beneficially modulates mindfulness scores. Furthermore, physiological and psychological surrogates improved to a meaningful extent following mindfulness practice, as well as performance outcomes in shooting and dart throwing. It seems reasonable to consider mindfulness practice strategies as a regular complementary mental skills training approach for athletes, at least in precision sports; however, more high-quality, randomized, controlled trials on mindfulness practice and performance improvements in diverse sport settings are needed.